PENERAPAN METODE KODALY UNTUK MENINGKATKAN KEMAMPUAN MEMBACA NOTASI SOLMISASI SISWA PADA MATERI SIMBOL NADA - Rahayu, Ayu Sri; Julia, Julia; Isrok'atun, Isrok'atun (Jurnal Pena Ilmiah, 2017)
The purpose of this research was to determine the process of implementing the Kodaly method in teaching art in elementary school, the results of its application and also the factors that support and hinder the process. The method used was descriptive qualitative. The research subject was 3rd grader SDN Bangkir. The study lasted three meetings. Data collection techniques in this study was the observation, documentation, interviews and questionnaires. The research instrument used was a guide observation, interview, test and non test. The findings of this study was an overview of each process application Kodaly method with the results of 80% of the students have knowledge of notation symbols and 82.5% of students can read the notation using techniques from Kodaly Method. Based on the observations that have been made of the factors that support and hinder the enthusiasm of learning, motivation and enthusiasm for learning of each student.